Combustion modelling of a rotary limekiln. (27th September 2010) - Macphee, James; Sellier, Mathieu; Jermy, Mark; Tadulan, Edilberto
Computational Fluid Dynamics (CFD) has been used to investigate the combustion processes occurring within a rotary lime kiln. Numerical results were validated against experimental data from the International Flame Research Foundation's (IFRF) Furnace No. 1. Results highlighted the need to reduce cold air leakages into the kiln and that firing the kiln with a 25/ thermal substitution of waste oil is the most efficient mode of operation. The work presented in this article will enable operating and environmental costs of the rotary kiln to be reduced and has laid the foundation for further investigations into the combustion of waste fuels in rotary kilns.